Creative language in advertising (based on English tourist advertising) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
Creative language in advertising is one of the ways of making advertising language seducing and attractive. Figures of speech are widely used in print advertising. Metaphor, pun, oxymoron, hyperbole, metonymy, irony and others can be shown as figures of speech used in advertising. Metaphor occurs as a result of comparison of one thing with others. Figures of speech are used in advertising to make the text of advertising expressive, attractive and memorable.
Keywords: advertising; metaphor; pun; alliteration; hyperbola; antithesis; rhyme; occasionalism; repetition; personification; oxymoron